The food nutrition label toward rural customer in Kelantan - Nor Atikah Mohd Abdullah (2016)
The nutrition food label is appeared on the label of a food product. It is to express the fact of the nutrient content of the food product. This is because consumers have a property to know about the nutrition content on the food product so that they would be purchasing in order to make appropriate decisions regarding their health and family. The content of the nutrition label on food products is a reference to the attitude, knowledge and perception of a customer. However, if trustworthy nutritional label are available, nutritional label could function as a search characteristics. They tend to consume food product which has food nutrition label so that they will get information from there. This study is focus on the effect of food nutrition toward rural consumer in Kelantan. A structured questionnaire was designed and used as an instrument to gather the information towards food nutrition label among rural customers. A survey was conducted and distributed to 189 respondents in rural Kelantan area. Descriptive statistics were used to analyze the data collected. Demographic factors such as age, level of education, race, gender, have been studied the effect towards food nutrition label. The respondents also indicate that food labels not only about nutrition information but they believe food products which have labels is quality products.